Role of staging laparoscopy in the stratification of patients with perihilar cholangiocarcinoma. Issue 4 (8th November 2016) - Bird, N.; Elmasry, M.; Jones, R.; Elniel, M.; Kelly, M.; Palmer, D.; Fenwick, S.; Poston, G.; Malik, H.
Abstract : Background: Cholangiocarcinoma is a rare cancer with a poor prognosis. Radical surgical resection is the only option for curative treatment. Optimal determination of resectability is required so that patients can be stratified into operative or chemotherapeutic treatment cohorts in an accurate and time‐efficient manner. Staging laparoscopy is utilized to determine the presence of radiologically occult disease that would preclude further surgical treatment. The aim of this study was to analyse the utility of staging laparoscopy in a contemporary cohort of patients with perihilar cholangiocarcinoma. Methods: Patients diagnosed with potentially resectable perihilar cholangiocarcinoma between January 2010 and April 2015 were analysed retrospectively from a prospective database linked to UK Hospital Episode Statistics data. Patients with distal cholangiocarcinoma and gallbladder cancer were excluded from analysis. Results: A total of 431 patients with perihilar cholangiocarcinoma were referred for assessment of potential resection at a supraregional referral centre. Some 116 patients with potentially resectable disease subsequently underwent surgical assessment. The cohort demonstrated an all‐cause yield of staging laparoscopy for unresectable disease of 27·2 per cent (31 of 114). The sensitivity for detection of peritoneal disease was 71 per cent (15 of 21; P < 0·001). The accuracy for all‐cause non‐resection for staging laparoscopy was 66 per cent (31 of 47) with a positive predictive value of progress to resection of 81 per cent (69 of 85). Neither the Bismuth–Corlette nor the Memorial Sloan Kettering Cancer Center preoperative scoring system was contingent with cause of unresectability at staging laparoscopy ( P = 0·462 and P = 0·280 respectively). Conclusion: In the present cohort, staging laparoscopy proved useful in determining the presence of radiologically occult metastatic disease in perihilar cholangiocarcinoma. Abstract : Laparoscopy may be beneficial